Dear Chandler, Dear Scarlett : a grandfather's thoughts on faith, family, and the things that matter most - Huckabee, Mike, 1955- (Sentinel, 2012)
Mike Huckabee--pastor, politician, governor, presidential candidate, talk show host, rock bassist, pundit, husband, and father--shares his love and wisdom with his grandson Chandler and granddaughter Scarlett, recounting heartwarming stories from his past and the bittersweet lessons learned along the way.